TATA KELOLA RUMAH KOS OLEH PEMERINTAH KOTA PEKANBARU TAHUN 2018 - Sarah Tamba; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Pekanbaru City Government has the authority to regulate its own area, including the residence category of boarding houses. Pekanbaru City is the Megapolitan City as the Capital of Riau Province with a population of more than 1 million. The role of the Pekanbaru City Government is needed to organize boarding house management, so as to create order, control and control in the licensing mechanism of boarding house management. But in reality, boarding houses in Pekanbaru City do not have their own legal basis. This happens because the City Government of Pekanbaru has not been maximized in managing the management. The formulation of the problem in this study is how the arrangement of boarding houses in Pekanbaru City.The purpose of this study was to determine the governance of boarding houses in Pekanbaru by the city government. This governance can be seen from the processes, regulations and relationships between institutions that are interrelated in managing the boarding house management.The concept of the theory I use is governance according to Cagin. This research uses a qualitative approach with descriptive methods. In collecting data, the writer uses interview and documentation techniques.The results of the author's research is that governance by the Pekanbaru City Government has not worked optimally. This can be seen from the Housing Control which includes Licensing, Arrangement and Ordering conducted by the Pekanbaru City Government. In the form of Licensing, there are several things that have become obstacles for the establishment of boarding houses, namely: the enactment of the Draft Regional Regulation on Regional Spatial Planning, only the enactment of the Permit to Establish a Temporary Building since 2016 ago, but in the imposition of the hotel tax base the boarding house category has been in 2011 For the Structuring itself there are 2 types, namely the arrangement carried out by the boarding-related owner of the establishment and operation of the boarding house, then the arrangement is carried out by the City Government based on the Regional Spatial Plan (RTRW). The last one is Law Enforcement, this is done by the Civil Service Police Unit (Satpol PP) based on the existing Public Order (Trantibum) principle. Then the writer also looked at the relationship between institutions in carrying out their respective duties and functions that were good enough. Keywords : Governance, Boarding House, City Government